STRATEGI EKSPOR SERAGAM MILITER INDONESIA KE AMERIKA SERIKAT DAN NEGARA-NEGARA EROPA OLEH PT. SRI REJEKI ISMAN (SRITEX) - Harum Anugerah Utami; Den Yelta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research describes the strategy of PT Sritex in exporting military uniforms to the United States and European countries. Comoditi non oil and gas exports that sed a in mainstay the Indonesian economy is textil . Value of textile comodity export is increasing year by year. As the largest textile company in Southeast Asia, PT Sritex is trusted to supply military uniforms to NATO, European countries and the United States. And also supplies for another 31 countries in the world. The research is descriptive quantitative method. All data and information are obtained from telephone interviews, journals, books, documents, company reports and online media. The focus of this research is how the strategy of exporting Indonesian military uniforms to United States and European countries by PT. Sritex . This research uses the perspective of liberalism and export theory and the theory of international cooperation.Strategies undertaken by PT Sritex in m export uniform military to America Union and Countries Europe is with enhancing capacity production and fixing planning system as well as the production process, availability high quality raw ingredients as important in the production process, scaling up diversification product, scaling up network with customers, approaching the destination of country export, increasesing efficiency of product, and developing of human resources.Keywords: Strategy, Exports, Military Uniforms, PT. Sritex,United States, European countries